2013
DOI: 10.1515/jgt-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Bounded presentations of Kac–Moody groups

Abstract: Abstract. In this article we extend the result of Guralnick, Kantor, Kassabov and Lubotzky to the affine Kac-Moody groups: we show that there exists a constant C > 0 such that every affine Kac-Moody group defined over a finite field F q , q 4 (with the exception of e A 1 and e A 1 ), has a presentation with l. / < C . We then derive the consequences of this result for the 2-spherical Kac-Moody groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Theorem 1.4(iii) of [2] gives the finite presentability of PSt A (R) if every pair of nodes of the Dynkin diagram lies in some irreducible spherical diagram of rank ≥ 3. (This use of a covering of A by spherical diagrams was also used by Capdeboscq [7].) By inspecting the list of affine Dynkin diagrams of rank > 3, one checks that this treats all cases of (i ) except A = α β γ δ (with some orientations of the double edges).…”
Section: Finite Presentationsmentioning
confidence: 99%
“…Theorem 1.4(iii) of [2] gives the finite presentability of PSt A (R) if every pair of nodes of the Dynkin diagram lies in some irreducible spherical diagram of rank ≥ 3. (This use of a covering of A by spherical diagrams was also used by Capdeboscq [7].) By inspecting the list of affine Dynkin diagrams of rank > 3, one checks that this treats all cases of (i ) except A = α β γ δ (with some orientations of the double edges).…”
Section: Finite Presentationsmentioning
confidence: 99%
“…Related results for other Kac-Moody groups over finite fields were also proved in [4]. As a consequence, the number of generators of a 2-spherical Kac-Moody group is independent of q and depends on the type of Dynkin diagram of G(q) rather than on the rank of G. We make use of this observation to provide bounds on the minimal number of generators of G(q).…”
Section: Introductionmentioning
confidence: 75%
“…In [1], Abramenko and Muhlherr have shown that with some restrictions (if the groups are 2-spherical, with some mild bounds on the size of F q ), Kac-Moody groups over F q are finitely presented with the number of generators depending on q and the Lie rank of G(q). 1 In [4], the author has shown that the family of affine Kac-Moody groups over F q (of rank at least 3) possesses bounded presentations: there exists C > 0 such that if G(q) is an affine Kac-Moody group of rank at least 3 corresponding to an indecomposable generalised Cartan matrix (IGCM) and q ≥ 4, then G(q) has a presentation with d(G) generators and r(G) relations satisfying d(…”
Section: Introductionmentioning
confidence: 99%
“…In recent years several papers have been dedicated to showing that finite simple groups or arithmetic groups have presentations with bounded number of generators and relations [KL06], [GKKL07], [GKKL08], [GKKL11], [Cap13]. This paper is about such quantitative results for some classes of profinite groups.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 0.1 is proved by combining the results of [Cap13] on bounded presentations of the discrete Kay-Moody group G(F q [t, t −1 ]), with the fact that it has the congruence subgroup property. It is important at this point to note that the above uniformness statement is not true globally, that is for abstract presentations of arithmetic groups obtained by replacing the local rings F q [[t]] by rings of integers of global fields (see §3 below).…”
Section: Introductionmentioning
confidence: 99%